Continuous thermic therapeutic ultrasound in sciatica experimental model (Fisioterapia e Pesquisa, 2009)
Therapeutic ultrasound is a physical therapy resource for relieving sciatic pain. The aim of this study was to assess the effectiveness of continuous therapeutic ultrasound in two different power densities (0,5 W/cm² and 1 W/cm²), on reducing pain in rats submitted to a sciatica experimental model. Twenty rats were used, divided into 3 groups: G1 (n=6) submitted to sciatica and placebo treatment; G2 (n=7) submitted to sciatica and treated with 0.5 W/cm² ultrasound; and G3 (n=7), submitted to sciatica and treated with 1 W/cm² ultrasound. Sciatica was provoked by surgical nerve compression on the right posterior limb of all animals. Treatment on the surgical procedure region consisted in ten daily 5-minute sessions, starting on the 3rd postoperative day. Pain was inferred by the time of paw elevation (TPE) during gait, measured before the surgery and on five further moments. Results showed TPE increase in all groups after surgery; but in both groups actually treated with ultrasound a significant TEP decrease was noticed, practically reaching initial values, the decrease being more precocious and intense in G2. Continuous ultrasound such as was delivered was hence effective in reducing sciatic pain.